Effect of Nano-Urea Based Nitrogen Application on the Growth, Phenology and Yield of Direct Seeded Rice (Oryza sativa L.) - , Sheikh Danish Bashir, Tauseef A. Bhat, Bilkees Jamsheed, Aijaz Nazir, Bisma Jan, Raihana Habib Kanth, Amal Saxena, Khursheed A. Dar, Inayat Mustafa Khan, Fehim Jeelani Wani, Ashu Sharma, Uma Naulia; et al. (Archives of Current Research International, 2024)
As large quantum of urea is used in the rice crop, there is a need to reduce atleast some portion of prilled urea to minimize the nitrogen losses besides improving the growth and yield of rice. With this rationale, a field experiment was carried out in the Kharif season of 2022 at the Agronomy Research Farm in Sher-e-Kashmir University of Agricultural Sciences and Technology- Kashmir, India to study the efficiency of Nano-urea over prilled urea in direct-seeded rice. The experimental study comprised of nine treatments viz.,T0 (Control), T1 (recommended dose of prilled urea), T2 (NU 2 sprays at 6 ml L-1 at AT and PI stage), T3 (NU 2 sprays at 8 ml L-1 at AT and PI stage), T4 (50 % RDPU as basal + NU 2 sprays at 2 ml L-1 at AT and PI stage), T5 (50 % RDPU as basal + NU 2 sprays at 4 ml L-1 at AT and PI stage), T6 (25 % RDPU as basal + NU 2 sprays at 2 ml L-1 at AT and PI stage), T7 (25 % RDPU as basal + NU 2 sprays at 4 ml L-1 at AT and PI stage), T8 (25 % RDPU as basal + NU 2 sprays at 6 ml L-1 at AT and PI stage) and T9 (25 % RDPU as basal + NU 2 sprays at 8 ml L-1 at AT and PI stage) which were arranged in randomized complete block design and replicated three times. These treatments included the application of Nano-urea in addition to conventional nitrogen dosages of 120 kg ha-1 and control treatments (no application). T5 (50 % RDPU as basal + NU 2 sprays at 4 ml L-1 at AT and PI stage) was the treatment that most significantly improved growth characteristics out of all of them, with a notable achievement of a Leaf Area Index (LAI) of 4.51. In addition, T5 performed superior to other treatments in yield-related parameters like panicle weight (2.69 g), yield (66.57 q ha-1). These findings demonstrate the significant potential of Nano-urea to maximize nitrogen use and increase yield in direct-seeded rice farming systems.